The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2340/16501977-1235
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity reconstruction in non-traumatic spinal cord injuries: An under-recognized opportunity

Abstract: Individuals with stable non-traumatic tetraplegia benefit from surgical rehabilitation of their upper extremities. The number of non-traumatic spinal cord injuries is likely to increase as lifespan increases worldwide, and further research into the functional rehabilitation of this population will therefore become increasingly relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…29 A number of papers have been published that describe technical aspects of safe surgical procedures, functional benefits and the importance of rehabilitation including early mobilization. 7, 8, 9, 10, 13 This study confirms previous results from patient-reported satisfaction surveys 17, 18, 19 indicating that surgery and rehabilitation is beneficial to the individual. Taking these findings into account, surgical restoration of upper limb function should be offered to all suitable candidates living with tetraplegia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…29 A number of papers have been published that describe technical aspects of safe surgical procedures, functional benefits and the importance of rehabilitation including early mobilization. 7, 8, 9, 10, 13 This study confirms previous results from patient-reported satisfaction surveys 17, 18, 19 indicating that surgery and rehabilitation is beneficial to the individual. Taking these findings into account, surgical restoration of upper limb function should be offered to all suitable candidates living with tetraplegia.…”
Section: Discussionsupporting
confidence: 86%
“…7 Advanced reconstruction of grip in tetraplegic patients is shown to improve upper-extremity performance, as well as supplying an increased level of independence and control in life. 8, 9, 10, 11, 12 Significant improvements in the basic activity of eating and more complex activities such as doing housework and taking part in leisure have also been shown. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Reconstructive surgery of the upper extremities using tendon transfer and joint stabilizations or, more recently, nerve transfer, has become an accepted part of rehabilitation of patients with cervical spinal cord injury (2,3). Numerous case series have demonstrated that key functions, such as elbow extension and handgrip can be restored reliably in individuals affected by traumatic or non-traumatic tetraplegia (4)(5)(6)(7)(8)(9)(10)(11). Consequently, the mobility, spontaneity and independence of tetraplegic individuals can be markedly and persistently increased (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%